2008
DOI: 10.1111/j.1524-4733.2007.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Patients by Antipsychotic Adherence Patterns Using Latent Class Analysis: Characteristics of Nonadherent Groups in the California Medicaid (Medi-Cal) Program

Abstract: Multiple indicators of adherence to antipsychotic medication can be used to define classes of adherence that are associated with patient characteristics and distinct patterns of prior health-care use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 16 publications
3
48
1
1
Order By: Relevance
“…In most Western countries, the prescription rate is below 10% of all antipsychotics. [2][3][4] This low rate is in contrast to evidence from naturalistic studies repeatedly demonstrating lower relapse and rehospitalization rates in patients receiving LAIs compared to oral treatment. [5][6][7] Although some colleagues might point out that recent randomized controlled trials (RCTs) [8][9][10] failed to corroborate results from the naturalistic studies, a broad consensus has developed that the patients in these RCTs (ie, those who are motivated to participate in a demanding clinical trial) are most likely not representative of those we see in our everyday clinical routine (ie, patients facing compliance problems).…”
contrasting
confidence: 53%
“…In most Western countries, the prescription rate is below 10% of all antipsychotics. [2][3][4] This low rate is in contrast to evidence from naturalistic studies repeatedly demonstrating lower relapse and rehospitalization rates in patients receiving LAIs compared to oral treatment. [5][6][7] Although some colleagues might point out that recent randomized controlled trials (RCTs) [8][9][10] failed to corroborate results from the naturalistic studies, a broad consensus has developed that the patients in these RCTs (ie, those who are motivated to participate in a demanding clinical trial) are most likely not representative of those we see in our everyday clinical routine (ie, patients facing compliance problems).…”
contrasting
confidence: 53%
“…The rate of non-adherence to psychotropic drugs in our dual diagnosed target population was 25.7%, lower than the non-adherence rate in the general psychiatric population, which ranges from 39% to 64.5%, depending on the study population, setting, and method of assessment (Ahn et al, 2008;Gilmer et al, 2004;Rascati et al, 2011;Sajatovic, Valenstein, Blow, Ganoczy, & Ignacio, 2006;Stephenson et al, 2012). Wu, Erickson, Piette, and Balkrishnan (2012), who conducted a study of antidepressant adherence among Medicaid enrollees with major depressive disorder, found that the average MPRm rate [MPRm = Number of days supply/(last claim date − index date + last days' supply)] was about 0.72 in those with comorbid anxiety.…”
Section: Discussionmentioning
confidence: 85%
“…Results of analyses of side effects with polytherapy are mixed. 7,9,[11][12][13][14][15] Adherence is decreased with antipsychotic polytherapy, 16 and the additional medication costs associated with antipsychotic polytherapy do not appear to be offset by cost savings in other areas of treatment. 17 Despite these mixed data, the use of antipsychotic polytherapy is common.…”
Section: -25mentioning
confidence: 99%